The Bahamas : 2003 Article IV Consultation-Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2003)
The Bahamas showed strong performance owing to its prudent macroeconomic management. Executive Directors welcomed this step, and emphasized the need to strengthen fiscal and international reserve positions, and diversify the economic base to maintain confidence and reduce economic vulnerabilities. They stressed the need to accelerate structural reforms, improve financial supervision and regulation, and to bring the regimes for combating money laundering and terrorism financing. They appreciated The Bahamas's participation in the General Data Dissemination System, and encouraged action to remove inconsistencies that exist in the economic data.